Contraceptive Use and Sanitary Napkin’s Types in Relation to Bacterial Vaginosis among Reproductive Age Females - Rabia Mukhtar, Aman-Ur-Rehman, Anum Ilyas, Momina Jahangir, Rajia Liaqat, Gohar Ali Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Bacterial vaginosis (BV) has been proposed as the most common vaginal disease among women of childbearing age as an adjunct to the development of cervical cancer. Previous studies of the relationship between BV and contraceptive use with sanitary practices as determinants have provided inconsistent and conflicting results. Aim: To determine the frequency of Bacterial vaginosis & find its association with contraceptive use and sanitary practices along marital status. Study Design: Cross sectional analytical study Place and duration of study: Department of Gynaecology, Sh. Zayed Hospital Lahore from 01-01-2016 to 31-10- 2016. Methodology: Two hundred and ninety six women of reproductive age group with complaint of vaginal discharge attending were enrolled. Proper history regarding age, marital status, use of contraceptive methods and sanitary practices was taken. Results: Disease prevalence was found to be 18.9%. Bacterial vaginosis was associated with age, type of sanitary napkins, and method of contraception, with adjusted odds ratios of 47.45, 279.9 and 172.0. However no association was found between the disease and marital status (as independent risk factor). Conclusion: Not using contraception and type of sanitary napkins are strongly related to occurrence of bacterial vaginosis in women of reproductive age group with vaginal discharge.